Influence of Real-Time Heating on Mechanical Behaviours of Rocks - Bin Gu; Zhijun Wan; Yuan Zhang; Yangsheng Ma; Xiaodong Bernard Xu (Advances in Civil Engineering)
The rock mechanical properties under the effect of high temperature present a great significance on underground rock engineering. In this paper, the mechanical properties of sandstones, marbles, and granites under real-time heating were investigated with a servo-controlled compression apparatus. The results show that mechanical behaviours of all the three types of rocks are influenced by real-time heating to different degrees. Due to thermal cracking, the uniaxial compressive strengths decrease as the heating temperature rises from room temperature to 400°C. Above 400°C, the sandstone exhibits a significant increase in UCS because of the sintering reaction. The sintering enlarges the contact area and friction between crystal grains in the sandstone, which strengthens the bearing capacity. For marbles, the UCS continues to decrease from 400°C to 600°C due to thermal cracking. However, the carbonate in the marble begins to decompose after 600°C. The generated particles would fill the cracks in the marble and increase the strength. For granites, their UCS presents a sharp decline after 400°C because of thermal cracking. For all rock elastic modulus, they present a decreasing trend, and this indicates that the rock’s ability to resist deformation gradually weakens under the effect of temperature. In general, rock mechanical behaviours under real-time heating differ from those in normal situations, and use of the parameters presented here is important for underground rock engineering related to high temperature and can improve the precision in theoretical and numerical analysis.